A portable device for fast analysis of explosives in the environment - Čapka, Lukáš; Večeřa, Zbyněk; Mikuška, Pavel; Šesták, Jozef; Kahle, Vladislav; Bumbová, Alena (Journal of chromatography. A, Including electrophoresis and other separation methods, 2015)
A novel portable device for fast and sensitive analysis of explosives in environmental samples is presented. The developed system consists of miniaturized microcolumn liquid chromatograph, photolytic converter and chemiluminescence detector. The device is able to determine selectively nitramine- and nitroester- and most of nitroaromates-based explosives as well as inorganic nitrates at trace concentrations in water or soil extracts in less than 8 min. The device allows to analyze various environmental samples such as soils or water materials without previous preconcentration. Because of internal power supply, the device ensures 12h of continuous operation. Limits of detection of compounds of interest are in the range of concentrations from 5.0 × 10(-9)M to 8.0 × 10(-5)M for a signal-to-noise ratio of 3. Limits of quantification are in the range of concentrations from 1.7 × 10(-8)M to 2.7 × 10(-4)M for a signal-to-noise ratio of 10. The repeatability of the method (RSD=2.9-5.6%) was determined by repeated injections (n=10) of the standard samples during 4h.
Keywords: Peroxynitrous Acid; Explosive Agents; Nitrates; luminiscenční měření; chromatografie kapalinová; poměr signál - šum; Aniline Compounds; Chromatography, Liquid; Nitrobenzenes; aniliny; kyselina peroxydusitá; voda; Water; nitrobenzeny; Signal-To-Noise Ratio; Soil; dusičnany; výbušné látky; půda; Luminescent Measurements